Kepemimpinan Kewirausahaan Pondok Pesantren dari Sisi Perempuan - Romadhon Assagaf; Nyayu Khodijah; Mgs Nazarudin (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 1970)
This article discusses women's leadership in increasing entrepreneurship in Darussalam Prabumulih Modern Islamic Boarding School. The purpose of this study was to see the leadership characteristics developed at the Modern Darussalam Prabumulih Islamic Boarding School in increasing entrepreneurship. This research method uses a qualitative method with a descriptive approach. Selection of informants by purposive sampling technique and snowball sampling technique. Data collection techniques using observation, interviews, documentation, and triangulation. The results show that the criteria for women's leadership through entrepreneurship are demonstrated through the ability to anticipate change, develop a vision, and strategy. Ability to anticipate changes made, among others, examine any changes that occur, develop alternatives, carry out evaluations and carry out monitoring actions. The ability to develop a vision includes focusing on organizational goals, developing a vision for the future of the organization, and always being aware of changing customer needs. Meanwhile, the ability to have a strategy in the form of formulation or planning, implementation or action, and evaluation stage. To increase entrepreneurial activities, it is necessary to carry out continuous activities by entrepreneurial leaders and administrators. Teamwork and communicationare the main keys to implementing an entrepreneurial activity program.